توريق القروض الرهنية أداة تمويلية لقطاع السكن في الجزائر - محمودي, بشير (University of Eloued جامعة الوادي, 2021)
اولنا في هاته الورقة البحثية معالجة تقنية حديثة في التمويل ألا وهو توريق القروض الرهنية في إطار تمويل السكن، والتي نظمها المشرع بموجب القانون رقم 06 – 05 المؤرخ في 20/02/2006، من خلالها وضحنا الإطار النظري للتقنية بتحديد مفهومها ثم تبيان أهميتها سواء لأطرافها أو للاقتصاد الوطني. كما عالجنا من حيث الإطار القانوني الأساس الذي يتم به التنازل عن تلك القروض ومراحلها، لنعرج عن دراسة تطبيق الجزائر لهاته التقنية. Abstract: In this paper, we tried to address a modern technique in financing, namely, the inclusion of collateral loans in housing finance, which was regulated by Law No. 06 - 05 of 20/02/2006, through which we clarified the theoretical framework of technology by defining its concept and then demonstrating its importance both to its parties and to the national economy. In terms of the legal framework, we have also addressed the basis for the waiver of such loans and their stages
Securitization of the mortgage loans a financing tool for Algeria's housing sector
مقال
Keywords: التوريق ; التمويل ; التنازل ; القروض الرهنية ; إصدار الأوراق المالية; Finance ; Securitization ; Waiver ; Mortgage Loans ; Issuance of Securities